The association of γδT lymphocytes with cystic leukomalacia in premature infants - Yuan, Mengjie; Jin, Xinyun; Qin, Fanyue; Zhang, Xiaoli; Wang, Xiaoyang; Yuan, Enwu; Shi, Ying; Xu, Falin (Frontiers in Neurology, 2022)
Background Periventricular leukomalacia (PVL) is an essential cause of cerebral palsy in preterm infants, and cystic PVL (cPVL) is the most severe form of the disease. The pathogenesis of cPVL is complex, and immune imbalances and inflammatory responses may play an essential role in it. Objective This study aimed to investigate the correlation between peripheral blood lymphocyte subsets, especially γδT cells with the pathogenesis of cPVL in preterm infants. Methods Peripheral blood from preterm infants with GA < 32 weeks and BW < 1,500 g was used in this study and was collected at 34 weeks corrected gestational age and within 24 h after the diagnosis with cranial MRI or cranial ultrasound. The infants were divided into cPVL groups and control groups. Flow cytometry was used to detect peripheral blood γδT, CD3+, CD4+, CD8+, and the proportion of total lymphocytes. Multiplex cell assays were used to detect the concentration of extracellular serum cytokines IL-6, IL-2, IL-8, IL-17A, IL-10, IL-1RA, eotaxin (CCL11), MCP-1 (CCL2), CXCL1, G-CSF, and IFNγ. A follow-up visit was carried out when the patient was 3 years old. Results After correcting for confounding factors, the proportion of peripheral blood γδT in the cPVL group was significantly lower than that in the control group (β: 0.216; 95% CI: 0.058–0.800, P < 0.022). Peripheral blood γδT (AUC: 0.722, P=0.006) and multivariate binary regression model (AUC: 0.865, P < 0.000) have good diagnostic values for cPVL. Peripheral blood γδT has some predictive power for neurodevelopmental outcomes in preterm infants (AUC: 0.743, P = 0.002). Conclusion It seems that peripheral blood γδT cells are inversely correlated with cPVL, which is not only a risk factor for cPVL disease but also neurodevelopmental outcomes in preterm infants. However, the causality of cPVL and various lymphocytes is unclear and needs further study.